ANALISIS MOTIVASI KERJA DALAM MENINGKATKAN KINERJA KARYAWAN DI HOTEL TAUFINA SOLOK - Vinuzula Hidayah; Novalinda (Jurnal Pariwisata Bunda, 2021)
This research was aimed to analyze the work motivation to empower the employees to give service excellent for their work performance. The rationales are that the more motivation the employees have, the more qualified work performance the employees perform.  To know this motivation, this research was conducted at Hotel Taufina, Solok, West Sumatera, Indonesia. In this research, 20 employees of Hotel Taufina answered questions on questionnaires. The questionnaires were about employees’ motivation seen from salary, incentive, work safety, protection, punishment, social sense as colleagues, teamwork, reward, opportunity for giving opinions, self-actualization, and work discipline. The finding of research revealed that Taufina hotel employees’ motivation was very good as indicated by the percentages  of all indicators above. It means that work motivations have met all what were demanded by each indicator in motivating employees to have their best work performance.